An Fe-doped NiTe bulk crystal as a robust catalyst for the electrochemical oxygen evolution reaction - Zhong, Lei; Bao, Yufei; Yu, Xu; Feng, Ligang (Chemical communications (Cambridge, England), 2019)
An Fe doped NiTe bulk crystal was demonstrated as a robust catalyst for the electrochemical oxygen evolution reaction. The promotion effect at least can be correlated with the significant electronic effect and the formation of lattice oxygen via bimetallic synergy by Fe doping. An Fe doped NiTe bulk crystal was demonstrated to exhibit an extremely active and stable performance for the electrochemical oxygen evolution reaction.